Critical assessment of the impact of HR strategies on employees' performance - Sana Anwaar; Ali Bin Nadeem; Misbah Hassan (Cogent Business & Management, 2016)
Line managers are considered as one of the greatest assets of a company. Therefore, it is vital to satisfy them and keep them actively engaged so that they can add value to the organization. This research explores the alternative Human Resource (HR) strategies to support line managers at Sainsbury's Southern. The research is based on semi-structured interviews conducted with line managers at various levels and across different departments of the company, aimed at exploring the perceptions and experience of the line managers in terms of HR devolution and the level of support provided to them by HR. Secondary data have been used to identify previous works on the topic of HR devolution as well as HR support to line and to also identify the various strategies to facilitate the line managers so that they can perform their new role more efficiently. The findings revealed that the trend of devolution has been successful as the employees interviewed are satisfied with the level of support provided to them by HR. However, some employees raised a few concerns i.e. inadequate training, unclear perceptions regarding the policies, increased workload, ineffective HR practices, etc., and feel that these need to be improved so that they can perform their new role more effectively.
Keywords: 650